2020
DOI: 10.1016/j.heliyon.2020.e05226
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone effects on healing efficacy, bone resorption and renal morphology of rats: histological and histometric study in rat calvaria

Abstract: Previous reports demonstrated the utility of systemic application of growth hormone (GH) in the treatment of bone defects. Very few studies correlated bone repair efficacy with hepatic and renal side effects promoted by locally-delivered GH. The objectives of this study were to assess the bone repair properties along with hepatic and renal adverse effects promoted by local application of GH in a rat model. Thirty-two rats were randomly divided (4 groups; n = 8/group), as follows: (i) AB (autogenous bone + loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…These results suggest that α-TCP scaffold may have improved osteoconductive capacity when rhGH is incorporated into its structure. In contrast to these results, Chaves et al recently showed that the utilization of autogenous bone grafts associated with local application and irrigation with 0.4 IU rhGH does not improve the bone repair in calvarial bone defects in Wistar rats [ 155 ]. Notably, many kidney alterations were observed in treated rats.…”
Section: Gh/igf and Oral Tissue Engineeringmentioning
confidence: 99%
“…These results suggest that α-TCP scaffold may have improved osteoconductive capacity when rhGH is incorporated into its structure. In contrast to these results, Chaves et al recently showed that the utilization of autogenous bone grafts associated with local application and irrigation with 0.4 IU rhGH does not improve the bone repair in calvarial bone defects in Wistar rats [ 155 ]. Notably, many kidney alterations were observed in treated rats.…”
Section: Gh/igf and Oral Tissue Engineeringmentioning
confidence: 99%